2014
DOI: 10.1088/2053-1591/1/4/046408
|View full text |Cite
|
Sign up to set email alerts
|

Orientationally textured thin films of WOxdeposited by pulsed laser deposition

Abstract: Pulsed laser deposition from a compound target in an oxygen atmosphere has been used to produce sub-stoichiometric WO x films of 30 nm thickness on Si(100) and SrTiO 3 (100)substrates. The growth temperature was 500°C and the pressure of the O 2 background was 2.5×10 -2 mbar. The films have been assessed using X-ray photoelectron spectroscopy, X-ray reflectivity, X-ray diffraction and scanning electron microscopy. The chemical shift of the tungsten 4f states showed that the tungsten was close to fully oxidised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Before use for deposition the target surface was cleaned in situ using a low laser fluence. The Loughborough PLD system [18,19] is based on a design by IWS Dresden [20] and has a base pressure of 2×10 -10 mbar. Deposition uses a pulsed and frequencydoubled Quanta Ray Nd:YAG laser operating at 10 Hz and wavelength 532 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Before use for deposition the target surface was cleaned in situ using a low laser fluence. The Loughborough PLD system [18,19] is based on a design by IWS Dresden [20] and has a base pressure of 2×10 -10 mbar. Deposition uses a pulsed and frequencydoubled Quanta Ray Nd:YAG laser operating at 10 Hz and wavelength 532 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The suitability of PLF WO 3 films for EC applications was investigated as a function of the partial oxygen pressure during deposition. Studies of the texture and morphology of PLD 30-nm thick WO 3 films deposited on Si(100) and SrTiO 3 (100) substrates under an O 2 background of 2.5 Pa showed that: (i) The laser fluence (in the range of 5 to 15 J·cm −2 ) strongly influences the texture, (ii) the films grown on STO are biaxially textured with a smooth surface, and (iii) films deposited on Si are granular [250]. The fabrication of WO 3 thin films with color neutrality for applications as EC materials was realized by the deposition of films containing 20% of vanadium onto SnO 2 :F coated glasses at T s = 20 • C under P O 2 = 10 Pa.…”
Section: Womentioning
confidence: 99%